Overview of Histone Deacetylase Inhibitors in Haematological Malignancies - H. Miles Prince; Simon Harrison; Mark J. Bishton; Ricky W. Johnstone; Michael Dickinson (MDPI AG, 2010)
Histone deacetylase inhibitors (HDACi) can induce hyperacetylation of both histone and non-histone target resulting in epigenetic reprogramming and altered activity, stability and localisation of non-histone proteins to ultimately mediate diverse biological effects on cancer cells and their microenvironment. Clinical trials have demonstrated single agent HDACi to have activity in hematological malignancies, in particular T-cell lymphoma and Hodgkin lymphoma. Combination strategies with standard therapies based on pre-clinical data are being employed with significant success due to their excellent side effect profile. Correlative studies will provide valuable information on the sub-groups of patients more likely to respond or be resistant to HDACi therapy, while long-term monitoring for toxicities is also needed.